Assessment of Executive Function Skills in Children with Isolated Growth Hormone Deficiency: A Cross-sectional Study - Gülsüm Yitik Tonkaz; Atilla Çayır (Galenos Yayincilik, 2024)
INTRODUCTION: The aim of this study was to evaluate executive function (EF), such as inhibition and working memory, in children with isolated growth hormone deficiency (IGHD) using performance-based tests and parent-report scales. METHODS: A total of seventy children between the ages of 7 and 12 years were included in the study. Half (n=35) had children with IGHD and half were healthy controls. To evaluate the EF performances of the participants, the Visual Aural Digit Span Test-B Form (VADS-B) and Stroop task were applied. EF was also evaluated using the Behavior Rating Inventory of Executive Function (BRIEF). RESULTS: Children with IGHD scored lower on the VADS-B form for short-term memory (p<0.05) compared to healthy controls. In addition, the completion time for the Stroop-color/word test was significantly longer in children with IGHD (p<0.05). For children with IGHD, their parents reported higher scores on all sub-scales of the BRIEF scale, with statistically significant differences for all sub-scales with the exception of "organization of materials" (p<0.05). DISCUSSION AND CONCLUSION: In this study, children with IGHD had poorer EF skills compared to unaffected peers. EF skills may influence academic success by affecting children's language skills, mathematical comprehension, cognitive flexibility, and hypothetical thinking. We believe that psychiatric evaluation of children with IGHD before and during treatment may positively contribute to both their academic performance and social relationships.